Thailand Economic Monitor, June 2020 : Thailand in the Time of COVID-19 - World Bank Group (World Bank, Bangkok, 2020)
The COVID-19 (coronavirus) shock hit Thailand in early 2020 adding to pre-existing vulnerabilities. Economic growth slowed from 4.2 percent in 2018 to 2.4 percent in 2019, with particularly weak performance in Q4 2019. The key drivers of slowing growth were weaker demand for exports reflecting the impact of US-China trade tensions, slowing public investments driven by delay in the passage of the FY 2020 budget, and a drought, impacting agricultural production. The COVID shock hit Thailand in early 2020 and has already had a significant economic impact, with a sharp growth contraction of 1.8 percent y-o-y and 2.2 percent q-o-q in Q1 2020. The Thai economy is projected to contract sharply in 2020, driven by a sharp deterioration in global and domestic demand. In the baseline, the economy is projected to contract by 5.0 percent in 2020, which is among the sharpest projected declines in the region. This is driven by a sharp decline in exports, particularly from tourism receipts and weakening global trade, and a slowdown in domestic demand reflecting the impact of mobility restrictions and mandated closures of businesses. The forecast is subject to future revisions, particularly on the downside, given heightened uncertainty surrounding the outbreak trajectory, globally and domestically.